Some features of the Rainfall over a belt in the Madras State (MAUSAM, 1963)
A study is made of the post monsoon rainfall over a belt of Madras State, where some Community Development Blocks are located, using the daily valu93 of rainfall recorded during the years 1948 to 1957. The special features of the rainfall as regards spatial distribution and intensity are discussed.